2022
DOI: 10.4209/aaqr.220213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Motor Vehicle Exhaust on the Air Quality of an Urban City

Abstract: The development of the economy and the prosperity of the industry have not only promoted the great progress of motor vehicle industry, but also made the number of motor vehicles in large and medium cities increase rapidly. In recent years, with the increasing number of urban motor vehicles, the environmental pollution caused by motor vehicle exhaust on both sides of the road has become increasingly serious. The high concentration of pollutants emitted by motor vehicles will seriously affect and threaten the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Furthermore, the emissions from motor vehicles harm the environment and atmosphere, resulting in adverse atmospheric phenomena, such as global warming and changes in the climate. [3][4][5][6][7] Pradeep et al 8 state that automotive vehicle manufacturers are actively researching lightweight materials for automotive vehicle applications. The intention is to enhance fuel efficiency by achieving a 6%-8% increase for every 10% reduction in vehicle weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the emissions from motor vehicles harm the environment and atmosphere, resulting in adverse atmospheric phenomena, such as global warming and changes in the climate. [3][4][5][6][7] Pradeep et al 8 state that automotive vehicle manufacturers are actively researching lightweight materials for automotive vehicle applications. The intention is to enhance fuel efficiency by achieving a 6%-8% increase for every 10% reduction in vehicle weight.…”
Section: Introductionmentioning
confidence: 99%
“…These emissions contribute to greenhouse gas emissions and smog, decreasing air quality and creating a risk to human health. Furthermore, the emissions from motor vehicles harm the environment and atmosphere, resulting in adverse atmospheric phenomena, such as global warming and changes in the climate 3–7 …”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of urban cities and the growth of the economy have accelerated the growth of the automobile industry as well as the rate at which vehicles are present in cities. In recent years, environmental pollution including PM 2.5 from motor vehicles has worsened [17,18]. Furthermore, it has been observed that PM 2.5 exhibits more favorable characteristics in high-income countries that have completed the stages of rapid urbanization and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, respiratory diseases and chronic obstructive pulmonary disease (COPD) are commonly found in urban areas [1][2][3]. Air pollutants emitted from traffic are major contributors to poor air quality in urban areas [4]. Nitrogen dioxide (NO 2 ) shows a relationship with traffic exposure, as well as with many other traffic-related pollutants [5,6].…”
Section: Introductionmentioning
confidence: 99%